1983
DOI: 10.1029/jc088ic02p01271
|View full text |Cite
|
Sign up to set email alerts
|

On the radiocarbon record in banded corals: Exchange parameters and net transport of 14CO2 between atmosphere and surface ocean

Abstract: We have made radiocarbon measurements of banded hermatypic corals from Florida, Belize, and the Galapagos Islands. Interpretation is presented here of these previously reported results. These measurements represent the 14C/12C ratios in dissolved inorganic carbon (DIOC) in the surface ocean waters of the Gulf Stream and the Peru Current at the time of coral ring formation. A depletion in radiocarbon concentration was observed in coral rings that grew from A.D. 1900–1952. It was caused by dilution of existing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 26 publications
3
103
0
Order By: Relevance
“…Patterns reveal differences between the -se and previously published data sets from Florida (Druffel and Suess 1983) and Bermuda (Druffel 1989). Comparisons are resented betw observed and model-calculated e14C trends for the temperate and tropical North Atlantic.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Patterns reveal differences between the -se and previously published data sets from Florida (Druffel and Suess 1983) and Bermuda (Druffel 1989). Comparisons are resented betw observed and model-calculated e14C trends for the temperate and tropical North Atlantic.…”
Section: Introductionmentioning
confidence: 85%
“…The Florida coral record is also shown for comparison (Druffel and Suess 1983). Prior to the introduction of bomb-produced 14C to the oceans (-1956-1958), the average pre-bomb A14C value from six measurements of the large Abrolhos coral (CABO) was -57.9 ± 4.5%o (sd).…”
Section: Methodsmentioning
confidence: 99%
“…Bomb-produced radiocarbon increased the A14C (per mil deviation with respect to the activity in 19th century wood) of the atmosphere to nearly 1000%o by 1964. In the surface ocean, the record of A14C is well documented in hermatypic corals [17][18][19][20][21] and exhibits an increase above the pre-bomb level starting in the late 1950's and continuing into the mid-1970's. This pattern of a4C variation with time has been used as a chronometer to determine the growth rate of the marine bivalve, Arctica islandica.…”
Section: Introductionmentioning
confidence: 97%
“…As they grow, these plants deposit calcium carbonate, which should contain chemical and isotopic records reflecting environmental conditions. Previous isotopic studies on coral and mollusks found that the amount of 14 C deposited as a part of the total carbon in biogenic carbonate records the 14 C concentration in the ocean water surrounding the organism (e.g., Druffel and Linick 1978;Nozaki et al 1978;Druffel and Suess 1983). This type of 14 C record should also be found in the carbonate of rhodoliths and can potentially be used as a record of climate variation.…”
mentioning
confidence: 99%